Pengenalan Koding dan Kecerdasan Artificial dengan Pendekatan Deep Learning di SD Inpres Cambaya IV - Muchtar, Fitriyanty; Nursalam, Nursalam; Sukmawati, Sukmawati; Amalia, Reski; Sentya, Mirna (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This Community Service Program (PKM) aims to describe the implementation and impact of the introduction of coding and artificial intelligence (AI) using a deep learning approach on fifth-grade students of SD Inpres Cambaya IV. The research subjects were 16 students who participated in coding and AI training activities in stages and contextually. This study used a descriptive qualitative approach with data collection techniques through observation, activity documentation, and student learning reflection. The results of the PkM activity showed that the introduction of coding and AI was able to increase students' enthusiasm, activeness, and initial understanding of the concepts of coding and artificial intelligence. Students showed a positive attitude, dared to try, and were able to re-explain the basic concepts learned in simple language. The deep learning approach plays a role in creating meaningful, enjoyable learning that is in accordance with the characteristics of elementary school students. This study recommends the integration of coding and AI as part of strengthening digital literacy in elementary schools.